Hak Ijbar Wali Tinjauan Maqashid Syari’ah dan Antropologi Hukum Islam - Muttaqin, Muhammad Ngizzul; Fadhilah, Nur (Fakultas Syariah, 2020)
Abstract:As an act determined by religion, marriage is a very sacred act, both in terms of religion and from the agreement between the husband and the wife. The sacredness in marriage certainly cannot be tainted by various aspects. Provisions regarding ijbar rights for the guardians need to be reviewed in terms of their relevance to maintain the holiness of marriage. In its way, the execution of ijbar rights has implications for the wife’s unwillingness. Whereas, the purpose of the application of Islamic law is to create justice and peace for humanity. Even from the community, the rules regarding the ijbar rights held by the guardians met pros and municipality. As literature-based research through extensive library studies, this paper attempts to reconcile the legal issues of ijbar rights from the viewpoint of the legal objectives (maqashid shari'a) and the conditions of culture and the culture of society (the anthropology of Islamic law). The findings in this study are: In the perspective of maqashid shari'ah, the practice of ijbar wali's right does not bring the basic principles of maqashid shari'ah. Namely the principle in creating happiness of calm, and peace in marriage, whereas in the anthropological perspective of Islamic law. The practice of rights ijbar guardian cannot be justified in the social sphere of society, confinement and restraints on women in the practice of ijbar rights are not in accordance with the current socio-cultural of society. So that the practice of ijbar rights cannot be accepted by the community.Keywords: Ijbar rights; maqashid shari’ah; anthropology of Islamic law.Abstrak:Sebagai perbuatan yang ditetapkan oleh agama, perkawinan merupakan perbuatan yang sangat sakral, baik dari segi agama, maupun dari sudut pandang perjanjian antara suami dan istri. Sakralitas dalam perkawinan tentu tidak bisa dinodai oleh berbagai aspek. Ketentuan tentang hak ijbar bagi wali, perlu dikaji kembali relevansinya guna menjaga sakralitas dalam perkawinan. Pelaksanaan hak ijbar berimplikasi pada ketidak relaan sang istri. Padahal, tujuan dari pemberlakuan hukum Islam adalah untuk menciptakan keadilan dan ketentraman bagi umat manusia. Dalam sudut pandang masyarakat pun, ketentuan mengenai hak ijbar yang dimiliki oleh wali menemui pro dan kontra. Sebagai penelitian berbasis litteratur melalui studi pustaka yang ekstentif, tulisan ini berupaya menyelaraskan kembali problematika hukum hak ijbar ditinjau dari sudut pandang tujuan hukum (maqashid syari’ah) dan kondisi kultur dan budaya masyarakat (antropologi hukum Islam). Temuan dalam penelitian ini adalah: dalam perspektif maqashid syari’ah, praktik hak ijbar wali tidak mendatangkan prinsip-prinsip dasar maqashid syari’ah, yaitu prinsip dalam menciptakan kebahagiaan, ketenangan, dan ketentraman dalam perkawinan, sedangkan dalam perspektif antropologi hukum Islam, praktik hak ijbar wali tidak bisa dibenarkan dalam ranah sosial masyarakat, keterkungkungan dan pengekangan terhadap perempuan dalam praktik hak ijbar tidak sesuai dengan sosio kultural masyarakat saat ini, sehingga praktik hak ijbar ini tidak bisa diterima oleh masyarakat.Kata Kunci: hak ijbar; maqashid syari’ah; antropologi hukum Islam.